2005
DOI: 10.1002/hlca.200590114
|View full text |Cite
|
Sign up to set email alerts
|

The Thermolysis of the Cycloadducts between Aryl Azides and Hexamethyl‐Dewar‐Benzene Revisited

Abstract: Dedicated to Professor Rolf Huisgen on the occasion of his 85th birthdayThe reactions of 1-azido-2,4,6-trimethyl-and 1-azido-2,6-dimethylbenzene with hexamethyl-Dewarbenzene (HMDB) give rise to the pentamethyl(iminoethyl)-4H-1,2-diazepines 4 and 5, respectively. The Xray crystal-structure analysis of 5 unequivocally established these unexpected structures, which motivated us to re-investigate the thermolysis of the adduct 1a of HMDB and azidobenzene. Previously, the triazonine 2 was reported to be the major pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Herein we report our preliminary results on the reaction between the dilithio reagents 1 and diazo compounds, in which diazo compounds acted as electrophiles. Multiply substituted 1-imino-pyrrole and indole derivatives were obtained in good to excellent isolated yields. , Synthetic methods for N -imino pyrrole and indole derivatives are very limited . A mechanistic investigation revealed that two diazo compounds reacted with one dilithio reagent affording the intermediate 2 .…”
mentioning
confidence: 99%
“…Herein we report our preliminary results on the reaction between the dilithio reagents 1 and diazo compounds, in which diazo compounds acted as electrophiles. Multiply substituted 1-imino-pyrrole and indole derivatives were obtained in good to excellent isolated yields. , Synthetic methods for N -imino pyrrole and indole derivatives are very limited . A mechanistic investigation revealed that two diazo compounds reacted with one dilithio reagent affording the intermediate 2 .…”
mentioning
confidence: 99%
“…During this doctoral study 16 molecular structures have been determined by X-ray crystallography as part of the cooperation with other groups. The cooperations with the groups of Dr. Breuning, Prof. Dr. Christl, Prof. Dr. Klingebiel, and Prof. Dr. Kost lead to five already printed publications [289][290][291][292][293] and two additional publications are in preparation or submitted.…”
Section: Crystallographic Cooperationsmentioning
confidence: 99%